Analysis of Legal Norms and Gender Equality in Relation to the Concept of Joint Custody for Minors - Muhammad Fadhlan Aziz; Muhamad Yogi Mubarok; Ahmad Rizki Nurfahillah; Ilman Napiah; Deden Najmudin (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
The application of custody rights in Indonesia generally uses sole custody. As stipulated in the Compilation of Islamic Law in Articles 105 and 156, priority for custody rights is automatically given to the mother. This is considered a problematic issue from a gender equality perspective, as child custody is not always monopolized by one gender but should consider aspects of quality, integrity, morality, and ability to fulfill the best interests of the child. At the same time, several court rulings in Indonesia have now established joint custody rather than sole custody. The purpose of this study is to re-examine the concept of joint custody of minor children as an effort and legitimization of the best interests of the child based on an analysis of legal norms and gender equality. This research is qualitative and uses a descriptive analytical method from library data sources. The results of this research can be concluded that joint custody is the granting of custody or care of the child to both parents alternately after divorce until both are required to take joint responsibility for their child. Although the granting of joint custody appears to deviate from existing provisions, it is not based on the provisions of the KHI but rather on the principle of the best interests of the child and the judge's legal interpretation. Furthermore, within the paradigm of gender equality, the role of men in contemporary society is equal to that of women, including in the care of minor children. This concept could serve as an alternative solution in resolving child custody disputes in Indonesia, simplifying the often complex and problematic process of determining custody rights.